SATU DIMENSI, DUA WAJAH: MEMETAKAN ORIENTASI KEUANGAN GENERASI Z DI SULAWESI TENGGARA ANTARA PERBANDINGAN SOSIAL DAN KEHATI-HATIAN FINANSIAL - Wa Ode Sartika; Samsul Bachri Soamole; Sitti Hadijah; Harpiang Wardingsih; Muhammad Suriyadarman Rianse; Muhammad Fajar Salemaku (JIEM : Journal Of International Entrepreneurship And Management, 2026)
This study aims to examine whether social comparison orientation, financial prudence, and financial management behavior form distinct constructs or merge into a single dimension among Generation Z in Southeast Sulawesi. The research method involved a questionnaire survey distributed to Gen Z respondents, analyzed through confirmatory factor analysis, the Fornell -Larcker criterion, the heterotrait-monotrait  ratio, and Harman’s single-factor test. The results indicate that discriminant validity failed across all construct pairs due to overlapping item contents. Consequently, the three constructs merged into a single bipolar continuum of financial orientation, ranging from social comparison to prudence. Furthermore, this financial orientation behavior is cross-segmental, showing no significant differences across demographic backgrounds. These findings highlight the critical importance of discriminant validity testing in financial behavior research & underscore the need for comprehensive financial education interventions to mitigate social comparison pressures.